Development of business performance model against customer's satisfaction factors using amos structural equation modeling software / Sa'diah Sahat, Razali Karim and Yap Bee Wah - Sahat, Sa'diah; Karim, Razali; Yap, Bee Wah (2006)
Delivering customer satisfaction has been a critical concept in contemporary thought and in research related to buyer behavior. It is generally argued that if customers are satisfied with a particular product or service offering after its use, then they are likely to engage in a repeat purchase and try line extensions. Satisfied customers are also likely to tell others of their favorable experiences and thus engage in positive word of mouth advertising. In the context of services, customer satisfaction is often described as being related to factors such as service quality and service features. Market research emphasizes that customer's satisfaction will lead to customer's retention and inevitably to better business performance. The main objective of this paper is to develop a Structural Equation Modeling (SEM) using AMOS to determine the most influential customers' satisfaction factors that give positive impact on business performance.